Redox-powered autonomous directional C–C bond rotation under enzyme control - Jordan Berreur; Olivia F. B. Watts; Theo H. N. Bulless; Nicholas T. O’Donoghue; Marc Del Olmo; Ashley J. Winter; Jonathan Clayden; Beatrice S. L. Collins (Nature, 2025)
Abstract Living biological systems rely on the continuous operation of chemical reaction networks. These networks sustain out-of-equilibrium regimes in which chemical energy is continually converted into controlled mechanical work and motion 1–3 . Out-of-equilibrium reaction networks have also enabled the design and successful development of artificial autonomously operating molecular machines 4,5 , in which networks comprising pairs of formally—but non-microscopically—reverse reaction pathways drive controlled motion at the molecular level. In biological systems, the concurrent operation of several reaction pathways is enabled by the chemoselectivity of enzymes and their cofactors, and nature’s dissipative reaction networks involve several classes of reactions. By contrast, the reactivity that has been harnessed to develop chemical reaction networks in pursuit of artificial molecular machines is limited to a single reaction type. Only a small number of synthetic systems exhibit chemically fuelled continuous controlled molecular-level motion 6–8 and all exploit the same class of acylation–hydrolysis reaction. Here we show that a redox reaction network, comprising concurrent oxidation and reduction pathways, can drive chemically fuelled continuous autonomous unidirectional motion about a C–C bond in a structurally simple synthetic molecular motor based on an achiral biphenyl. The combined use of an oxidant and reductant as fuels and the directionality of the motor are both enabled by exploiting the enantioselectivity and functional separation of reactivity inherent to enzyme catalysis.